Mesolimbic Dopamine Super-Sensitivity in Melanin-Concentrating Hormone-1 Receptor-Deficient Mice - Smith, Daniel G; Tzavara, Eleni T; Shaw, Janice; Luecke, Susan; Wade, Mark; Davis, Richard; Salhoff, Craig; Nomikos, George G; Gehlert, Donald R (The Journal of neuroscience, 2005)
Melanin-concentrating hormone (MCH) neurons and MCH-1 receptors (MCH1r) densely populate mesolimbic dopaminergic brain regions such as the nucleus accumbens (NAc). The regulation of dopamine by MCH1r was suggested to be an important mechanism underlying the hyperactive phenotype of MCH1r knock-out (ko) mice. However, MCH1r modulation of monoamine neurotransmission has yet to be examined. We tested whether dopamine, norepinephrine, and serotonin function is dysregulated in MCH1r ko and wild-type (wt) mice. MCH1r ko mice exhibited robust hyperactivity in a novel or familiar environment and were super-sensitive to the locomotor activating effects of d -amphetamine and the D 1 agonist 2,3,4,5-tetrahydro-7,8-dihydroxy-1-phenyl-1H-3-benazepine HCl. The D 2 agonist, quinpirole, decreased locomotion similarly in both ko and wt mice. Tissue contents of dopamine within the NAc and caudate-putamen were not significantly different in ko compared with wt mice. Basal and amphetamine-evoked NAc dopamine, norepinephrine, and serotonin efflux, as measured using in vivo microdialysis, were not significantly different between genotypes. In contrast, D 1 -like and D 2 -like receptor binding were significantly higher within the olfactory tubercle, ventral tegmental area, and NAc core and shell of ko mice. Norepinephrine transporter (NET) binding was significantly elevated within the NAc shell and globus pallidus of ko mice, whereas serotonin transporter binding was decreased in the NAc shell. Thus, deletion of MCH1r results in an upregulation of mesolimbic dopamine receptors and NET, indicating that MCH1r may negatively modulate mesolimbic monoamine function. MCH1r may be an important therapeutic target for neuropsychiatric disorders involving dysregulation of limbic monoamine systems.